Occupational health in the era of climate change and the green transition: a call for research - Michelle C. Turner; Xavier Basagaña; Maria Albin; Karin Broberg; Alex Burdorf; Kim R. van Daalen; Irina Guseva Canu; Henrik A. Kolstad; Manolis Kogevinas; Rachel Lowe; Neil Pearce; Frank Pega; et al. (The Lancet Regional Health. Europe)
Summary: Work and working conditions are fundamental social determinants of health. Climate change poses an urgent and growing threat to workers' health, through both direct exposure to environmental hazards and indirect exacerbation of social and health inequalities. Occupational health, which focusses on the promotion of mental and physical health and well-being of workers, is a key but often overlooked area in this context. Research at the intersection of climate change and occupational health remains limited. At the same time, climate change mitigation and adaptation efforts are driving rapid transformations in the workplace, including shifts towards sustainability and circular economy models. These transitions are creating new occupational hazards, including in renewable energy and circular economy sectors. We argue for increased investment in occupational health research and surveillance to address the evolving impacts of both climate change and the green transition, to better promote and protect workers’ health and rights.